KOH activation of biomass-derived nitrogen-doped carbons for supercapacitor and electrocatalytic oxygen reduction. (20th January 2018) - Lin, Gaoxin; Ma, Ruguang; Zhou, Yao; Liu, Qian; Dong, Xiaoping; Wang, Jiacheng
Abstract: Nitrogen-doped porous carbon has aroused extensive interests owing to its unique physical and chemical properties. However, the complicated nitrogen-doping method and high cost limit its practical application. In this work, the nitrogen-rich biomass soybean was used as a single precursor for both carbon and nitrogen source to prepare nitrogen-doped hierarchical micro-mesoporous carbon via templating carbonization coupling with subsequent KOH activation. The influence of KOH dosage on the morphology, structure and electrochemical performance (supercapacitor and oxygen reduction reaction (ORR)) was studied in detail. The optimized ANPC-3, synthesized under the KOH/carbon mass ratio of 3/1, possesses high specific surface area of 1749 m 2  g −1, developed hierarchical micro-mesoporous structures as well as moderate nitrogen content (1.37 at.%). ANPC-3 exhibits a large energy density of 12.5 Wh kg −1 at a power density of 450 W kg −1 with excellent charge-discharge cyclic stability of 96.5% capacitance remaining after 5000 cycles. As an ORR electrocatalyst, it shows improved ORR activity as well as much better stability and methanol-tolerance capacity than commercial Pt/C catalyst. The unique hierarchical micro-mesoporous textures, high surface area and moderate N-doping level make biomass-derived ANPC-3 become an excellent electrode material in various applications. Graphical abstract: A series of biomass-derived hierarchical porous nitrogen-doped carbons have been prepared from nitrogen-rich soybean via templating carbonization coupling with subsequent KOH activation, which could be used as high-performance electrode materials for supercapacitor and electrocatalytic oxygen reduction. Image 1